Bi-objective optimization of multi-server intermodal hub-location-allocation problem in congested systems: Modeling and solution - Mahdi Rashidi Kahag; Seyed Taghi Akhavan Niaki; Mehdi Seifbarghy; Sina Zabihi (Journal of Industrial Engineering International, 2019)
A new multi-objective intermodal hub-location-allocation problem is modeled in this paper in which both the origin and the destination hub facilities are modeled as an M/M/m queuing system. The problem is being formulated as a constrained bi-objective optimization model to minimize the total costs as well as minimizing the total system time. A small-size problem is solved on the GAMS software to validate the accuracy of the proposed model. As the problem becomes strictly NP-hard, an MOIWO algorithm with an efficient chromosome structure and a fuzzy dominance method is proposed to solve large-scale problems. Since there is no benchmark available in the literature, an NSGA-II and an NRGA are developed to validate the results obtained. The parameters of all algorithms are tuned using the Taguchi method and their performances are statistically compared in terms of some multi-objective metrics. Finally, the entropy-TOPSIS method is applied to show that MOIWO is the best in terms of simultaneous use of all the metrics.
Keywords: 650; Intermodal P-hub median problem; Queuing systems; Multi-objective invasive weed optimization; Entropy-TOPSIS method